Characteristics of quails egg's quality - ΓΙΑΝΝΑΚΟΠΟΥΛΟΣ, Α. Λ.; ΤΣΕΡΒΕΝΗ-ΓΟΥΣΗ, Α. Σ. (Journal of the Hellenic Veterinary Medical Society, 2019)
The eggs used in this study were laid by Coturnix coturnix japonica quails, during their 7th to 22th weeks of laying production. A total of 280 eggs collected twice daily in last three days of 7th, 8th, 10th, 11th, 12th, 14th, 17th and 22th weeks were used to investigate egg quality and egg shell strength under typical greek farming conditions. The results drawn from this study were as follows: 1. The egg weight increased significantly (P<0.001) from 11.33 g on the 7th week to 12.95 g on the 22th, while the shell weight increased (P<0.05) only by 0.07 g. 2. The yolk weight increaced by 0.51 g (Ρ 0.001), while the albumen weight increased (P<0.05) by 0.28 g. 3. The participation of yolk weight, albumen weight, and the shell weight to the total egg weight was 32.59%, 53.57%, and 7.80%, respectively. 4. Significant (P<0.01) regressions between the egg's characteristics and the quail's age were obtained with R' values ranging from 0.18 to 0.75. In addition significant correlation (Ρ 0.001) of egg's shape with albumen weight, and specific gravity were found with r=0.8160 and r=7878, respectively. The conclusions were that the egg's shell strength and the egg's characteristics were modified as the quails aged. Also the best criterion for the shell's strength was the egg shape index.